Independent appraiser assessment of the quality, methodological rigour and transparency of the development of the 2008 international consensus statement on concussion in sport - White, P. E.; Shee, A. W.; Finch, C. F. (British Journal of Sports Medicine, 2014)
Aim: In recent years, considerable effort has been devoted to the development and revisions to an international consensus statement on concussion in sport (ICSCS). The aim of this study was to obtain expert views on the methodological rigour and transparency with which the 2008 ICSCS was developed, as a precursor to the development of the 2012 update. Methods: Delegates registered for the 2012 fourth International Conference on Concussion in Sport, selected local concussion researchers not involved in any prior international consensus meetings, and all authors of the 2008 ICSCS published paper were invited to assess the methodological rigour and transparency with which the 2008 ICSCS was developed. The online Appraisal of Guidelines for Research and Evaluation (AGREE) II assessment tool, with six quality domains, was used and domain scores were expressed as a percentage of the maximum possible score for that domain. Results: 18 appraisers completed the online AGREE II assessment. Ten appraisers said they would recommend the 2008 ICSCS for use (without modification) and seven said they would recommend its use with some modification. The `scope and purpose` and `clarity of presentation` were rated highest, both scoring 78%. The lowest scoring domain was `applicability` with a score of 55%. Conclusions: The quality of the ICSCS is important because it is used to guide return-to-play decisions and the management of sport-related concussions. This appraisal of the 2008 ICSCS suggests that a greater focus is needed on the actual implementation of future ICSCS and the relationship between implementation and desired health outcomes.